Cesaro Supermodular Order and Archimedean Copulas - H.R. Nili Sani; M. Amini; M. Khanjari (Journal of Sciences, Islamic Republic of Iran)
In this paper, we introduce a new kind of order, Cesaro supermodular order, which includes supermodular order and stochastic order. For this new order, we show that it almost fulfils all desirable properties of a multivariate positive dependence order that have been proposed by Joe (1997). Also, we obtain some relations between it with other orders. Finally, we consider different issues related extended Archimedean copula and positive dependence.